Active and Passive Control of an Exoskeleton with Cable Transmission for Hand Rehabilitation - Wang Shuang; Li Jiting; Zhang Yuru; Wang Ju (2009 2nd International Conference on Biomedical Engineering and Informatics, 2009)
This paper investigates the control algorithm of an exoskeleton for hand rehabilitation, which accomplishes both active and passive control mode. A double closed loop control structure is developed, which consists of position control loop and compensation control loop. The position controller is based on impedance control. The compensation controller is used for compensating the position error caused by deflection of the cable and sheath in the mechanical transmission. To realize the compensation, the spring model is used to represent the elasticity of the cable and sheath. With the proposed method, the maximum joint position error is about 1.5 degree, which satisfies the requirement in hand rehabilitation application. The experimental result demonstrates the validity of the propose method.